The Effect of Word of Mouth and Place on Brand Aware Mixue in Malang City - Aris Enrico Sukemi; Seno Aji Wahyono; Santi Widyaningrum (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to analyze whether the use of word of mouth and place influences the brand awareness of the people in Malang City. The population selected in this study is all people who have bought Mixue products at outlets in Malang City. Using a survey data collection method, namely a questionnaire (Google Form) with a total of 193 respondents. Using multiple linear regression analysis techniques this was done because the analysis in this study needed to determine the influence of more than one independent variable on one dependent variable. The results of this study indicate that there is a positive influence between word of mouth and place on the brand awareness of Mixue in Malang City.